IMPLEMENTASION OF PROJECT BASED LEARNING TO INCREASE COLLABORATION AND RESPONSIBILITY IN EARLY CHILDHOOD - Nurbelawati Nurbelawati; Nina Kurniah (UNIB Press, 2019)
The purpose of this study was to describe the application of the Project Based Learning method in improving the ability of collaboration and responsibility of early childhood with lego media in the vilage group b in the district of lebong. This stud uses classroom action research. The subject of this research is a group of children at the village of Al Karomah audited in the district of lebong, amounting to 15 children Regency consisting of 8 men and 7 women. Data collection tecniques use a observation sheet on responsi bility and collaboration. Data analysis uses mean and t test. The results of the study showed very significant results berween the ability of collaboration in cycles 1 by 73.3%, the second cycle by 80% and the third cycle by 100%. the ability to responsibility also increased from cycle 1 by 66.6%, the second cycle was 73.3% and the third cycle increased to 100%. Based on the results of this study, Project Based Learning drawings are recommended to collaboration and responsibility and become the right alternative for learning